2022
DOI: 10.1371/journal.pone.0278627
|View full text |Cite
|
Sign up to set email alerts
|

Optimising a method for aragonite precipitation in simulated biogenic calcification media

Abstract: Resolving how factors such as temperature, pH, biomolecules and mineral growth rate influence the geochemistry and structure of biogenic CaCO3, is essential to the effective development of palaeoproxies. Here we optimise a method to precipitate the CaCO3 polymorph aragonite from seawater, under tightly controlled conditions that simulate the saturation state (Ω) of coral calcification fluids. We then use the method to explore the influence of aspartic acid (one of the most abundant amino acids in coral skeleto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 50 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…It is important to note that our experiment, like most FEA, does not consider the role of organics between calcite layers or around individual crystals which could play a role in enhancing hardness [ 60 ]. It has been shown in taxa with very different calcification processes and mineralogy that they increase skeletal organic content under conditions of ocean acidification [ 61 63 ] though this does not appear to impact hardness significantly [ 64 ]. Moreover, as foraminifera have very low organic content in their shells, ranging between 0.04% and 0.1% [ 65 , 66 ], we assume that this is not likely to have a significant effect.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that our experiment, like most FEA, does not consider the role of organics between calcite layers or around individual crystals which could play a role in enhancing hardness [ 60 ]. It has been shown in taxa with very different calcification processes and mineralogy that they increase skeletal organic content under conditions of ocean acidification [ 61 63 ] though this does not appear to impact hardness significantly [ 64 ]. Moreover, as foraminifera have very low organic content in their shells, ranging between 0.04% and 0.1% [ 65 , 66 ], we assume that this is not likely to have a significant effect.…”
Section: Discussionmentioning
confidence: 99%
“…However, under the conditions of this study, i.e., with liquid alkaline material, the Ωaragonite threshold for the initiation of spontaneous pseudo-homogeneous carbonate formation in particle-free seawater is approximately 11.3 at a salinity of 32.6 and ~11°C (Marion et al, 2009based on data from Morse & He, 1993. Most ocean surface waters are naturally oversaturated with carbonates (Ωaragonite ~2-5, Olsen et al, 2018), yet no obvious spontaneous inorganic carbonate formation is occurring., as the presence of Mg 2+ (Berner, 1975;Pan et al, 2021), phosphate (Burton & Walter, 1990), and dissolved organic matter species (Chave & Suess, 1970;Kellock et al, 2022) are known to delay or inhibit precipitation of CaCO3. Since Mg 2+ in an open ocean context correlates to salinity, its concentration could vary depending on the local conditions (Moras et al, 2023), while phosphate and DOM concentrations are related to biological processes and seasonal changes.…”
Section: Nucleation Phasementioning
confidence: 99%
“…Studies have shown that Asp is a broad-spectrum mediator that can act on almost all phases of calcium carbonate in vitro. It can stabilize and extend the lifetime of amorphous calcium carbonate (ACC) [ 6 , 7 ], increase the hardness of calcite single crystals [ 8 ], and even promote or inhibit aragonite precipitation under certain conditions [ 9 , 10 ]. However, the most reported effect of Asp is that it can induce the formation of vaterite [ 11 , 12 ], even though this is usually thermodynamically disfavored.…”
Section: Introductionmentioning
confidence: 99%